Rice cultivars affect fitness-related characteristics and digestive physiology of the rice weevil, Sitophilus oryzae (L.) (coleoptera: Curculionidae). (September 2021) - Jalaeian, Mahdi; Mohammadzadeh, Mozhgan; Mohammadzadeh, Mohammad; Borzoui, Ehsan
Abstract: The rice weevil, Sitophilus oryzae (L.), is one of the main pests of rice and other stored grains. Due to the negative effects of synthetic pesticides on the environment and non-target organisms, more environmentally benign alternative control techniques are needed for controlling pests. In the present study, the development, reproduction, and digestive enzyme activity of Sitophilus oryzae (L.) were evaluated on 12 rice cultivars under laboratory conditions [28 ± 1 °C, 60 ± 5% RH, and a photoperiod of 16:8 (L: D) h]. Among tested rice cultivars, the developmental time of S. oryzae immature stages was the shortest on DomSiah (33.0 days), Hashemi var. Guilan (34.0 days) and Hashemi var. Mazandaran (34.0 days) and the longest on Neda (44.5 days). The highest fecundity was recorded for beetles reared on cultivars DomSiah (316.8 eggs), Hashemi var. Mazandaran (301.1 eggs), and Hashemi var. Guilan (293.3 eggs); and the lowest for beetles reared on cultivar Neda (147.0 eggs). The highest survival of immature stages was recorded on cultivars Hashemi var. Mazandaran (80.0%), AliKazemi (75.2%), DomSiah (73.6%), and Hashemi var. Guilan (71.0%) whereas those on cultivar Neda (25.3%) had the lowest survival. The female adults that developed from larvae reared on cultivars Neda, Govhar, and Fajr had the lowest body mass (67.7, 68.6, and 69.4 mg). Also, the males' mass was the lowest on cultivars Neda, Fajr, Shiroudi, and Govhar (60.7, 62.2, 62.9 63.3 mg, respectively). The adults developed from larvae reared on cultivars Fajr and Neda had the lowest levels of α-amylase activity (1.77 and 1.64 mU/min/individual, respectively). Also, those reared on cultivar Neda had the lowest levels of protease activity (0.067 OD/min/individual). Results suggest cultivar Neda, as an unsuitable food for S. oryzae development that negatively affects the amylolytic and proteolytic activity of this pest, could be considered in the integrated management programs of this pest. Highlights: Sitophilus oryzae (L.) is one of the main pests of rice and other stored grains. The developmental time of S. oryzae immature stages was the shortest on DomSiah, Hashemi var. Guilan and Hashemi var. Mazandaran and the longest on Neda. The highest fecundity was recorded for beetles reared on cultivars DomSiah, Hashemi var. Mazandaran, and Hashemi var. Guilan; and the lowest for beetles reared on cultivar Neda. The adults developed from larvae reared on cultivars Fajr and Neda had the lowest levels of α-amylase activity. Those reared on cultivar Neda had the lowest levels of protease activity. Results suggest cultivar Neda, as an unsuitable food for S. oryzae development that negatively affects the amylolytic and proteolytic activity of this pest, could be considered in the integrated management programs of this pest